Empirical Evidences on Social Entrepreneurship in Malaysia: A Structural Equation Modelling Approach - Sarwar, Abdullah Al-Mamun; Mhd. Sarif, Suhaimi (Kulliyyah of Economics and Management Sciences, IIUM, 2021)
This chapter argues that empirical evidences on social entrepreneurship in Malaysia from a Structural Equation Modelling approach. This approach is reasonable to gauge key variables for social entrepreneurship research. In Malaysian context of social entrepreneurship, there should be some specific policies which will help to build the social entrepreneurship. With these policies are taken for social entrepreneurship, the social entrepreneurs can help building the Malaysian society which are not available at free of costs for the society as well.